Prevalence and risk factors of reduced bone mineral density in HIV infected individuals / Sheron Goh Sir Loon - Sheron Goh, Sir Loon (2018)
The commencement of antiretroviral therapy (ART) in human immunodeficiency virus (HIV)-infected individuals has decreased HIV-related complications and improved survival. However, studies have shown that there is a higher prevalence of osteopenia/osteoporosis [reduced bone mineral density (BMD)] in HIV-infected individuals. The aim of our study was to determine the prevalence of osteopenia/osteoporosis (reduced BMD), vitamin D level, the 10-year probability of fracture risk, and its associated risk factors in HIV-infected and HIV-uninfected individuals in Malaysia. HIV-infected individuals aged ≥25 years and virologically suppressed on ART for at least 1 year, were recruited from September 2014-September 2016, at a tertiary hospital in Malaysia. HIV-uninfected individuals were recruited from the community. BMD was assessed using dual X-ray absorptiometry (DXA), whilst the 10-year probability of fracture risk was calculated using the fracture risk assessment tool (FRAX®). A total of 684 potential participants were approached; of which 640 participants agreed to participate (response rate=93.6%). Participants were then matched for gender and age, finally giving 206 participants in each group. The majority of participants were male (73.8%) and Chinese (64.1%) with the median age of 40 years old. A significantly higher number of HIV-infected individuals (73.8%) had reduced BMD when compared to HIV-uninfected individuals [(57.3%), p<0.001]. The prevalence of osteoporosis was found to be significantly higher in HIV-infected individuals (14.1%) when compared to HIV-uninfected individuals [(5.3%), p<0.001]. Similarly, vitamin D deficiency (<50nmol/L) was significantly higher in HIV-infected (65.0%) compared to uninfected individuals [(30.1%), p<0.001]. The 10-year probability of sustaining a hip v fracture in HIV-infected individuals (0.4%) was significantly higher than in HIVuninfected individuals (0.2%, p=0.003), but not in major osteoporotic fracture [HIVinfected (1.7%); HIV-uninfected (1.3%)] (p=0.066). Lower body mass index (BMI), reduced physical activity and older age were risk factors that significantly associated with reduced BMD in HIV-infected individuals. In conclusion, the prevalence of reduced BMD, vitamin D deficiency and the 10-year probability of sustaining a hip fracture was higher in HIV-infected compared to HIV-uninfected individuals. Lower BMI, reduced physical activity and older age were found to be associated with reduced BMD in HIVinfected individuals.